Influence of Inflow Turbulence on the Flow Characteristics around a Circular Cylinder - Jianfeng Yao; Wenjuan Lou; Guohui Shen; Yong Guo; Yuelong Xing (Applied Sciences, 2019)
To study the influence of turbulence on the wind pressure and aerodynamic behavior of smooth circular cylinders, wind tunnel tests of a circular cylinder based on wind pressure testing were conducted for different wind speeds and turbulent flows. The tests obtained the characteristic parameters of mean wind pressure coefficient distribution, drag coefficient, lift coefficient and correlation of wind pressure for different turbulence intensities and of Reynolds numbers. These results were also compared with those obtained by previous researchers. The results show that the minimum drag coefficient in the turbulent flow is basically constant at approximate 0.4 and is not affected by the turbulence intensity. When the Reynolds number is in the critical regime, the lift coefficient increased sharply to 0.76 in the smooth flow, indicating that flow separation has an asymmetry; however, the asymmetry does not appear in the turbulent flow. Drag coefficient decreases sharply at a lower critical Reynolds number in the turbulent flow than in the smooth flow. In the smooth flow, the separation point is about 80° in the subcritical regime; it suddenly moves backwards in the critical regime and remains almost unchanged at about 140° in the supercritical regime. However, the angular position of the separation point will always be about 140° for turbulent flow for the Reynolds number in these three regimes. Turbulence intensity and Reynolds number have a significant effect on the correlation of wind pressures around the circular cylinder. Turbulence will weaken the positive correlation of the same side and also reduce the negative correlation between the two sides of the circular cylinder.